Dental auxiliaries versus community health workers: similarities and contrasts - Simone De Melo Costa; Flávia Ferreira Araújo
INTRODUCTION: The dental auxiliaries and the community health workers (CHWs) are practitioners that represent an important part in the Family Health Policy in Brazil and have several tasks. OBJECTIVE: To analyze the attributes of the dental auxiliaries and of the CHWs, regarding the application of their services and their education/training, to identify the similarities and contrasts between these health care practitioners. METHODOLOGY: Quantitative and census method data collection performed on the context of the Education Program for Health Workers - PET‑Saúde, 2010‑2012. The data collection method was a semi-structured questionnaire. The analysis has a level of significance of p<0.05. RESULT: In this paper, 29 dental auxiliaries and 241 CHWs have participated in the surveys. The assignments that take place on the community context, such as home visits were more associated to the CHWs (p<0.05). On the other hand, the activities that happen on a clinical environment, such as providing assistance to graduated health professionals and performing clinical procedures, are more commonly performed by the dental assistant (p<0.05). Both categories presented similarities performing preventive health care, teamwork analysis, informative initiatives and community mobilization routines (p>0.05). CONCLUSION: Similarities and contrasts were identified between these health care workers. The dental auxiliaries, despite being mostly issued to specific assignments on a clinical environment, are able to shift their praxis by taking actions on a family and community context once integrated to a family health team.